Hair extractor comb - Sa’ait, Noraini; Kanyan, Agnes; Abdullah, Nur Liyana; Hamzah, Nur Balqis Amirah; Abdul Rahman, Nur Ellyssa Azreen; Mohamad Mokhaldin, Siti Nasuha Nabilah; Yusmandi, Yusratul Wanie (Universiti Teknologi MARA, Kedah, 2023)
Humans frequently struggle with hair loss, which makes it easy for their hair to become tangled in combs. As a result, it will be quite unsanitary for them since these hairs will begin to collect on the comb and spread bacteria there. A hair extractor comb is the thing our team has decided to make to address this issue. This comb's purpose is to make it simple to remove hair that has become trapped on it. Our comb is unique from other combs since it has a hair extractor because the combs, we typically use every day do not have the capacity to remove our hair if it becomes trapped on the comb. As a result, it became a reason for people to use our product to make life more convenient for them. Due to the huge user bases that Shopee and TikTok shop have, they will serve as our primary distribution channels for our items. Additionally, we'll use social media to advertise our product's specifics to gain more potential customers in the future. We hope that through the invention of this product, it can help those who have hair fall problems to live their life easily.